A time and frequency domain analysis of the effect of vibrating fuel assemblies on the neutron noise. (March 2020) - Vidal-Ferràndiz, A.; Carreño, A.; Ginestar, D.; Demazière, C.; Verdú, G.
Highlights: This work studies the neutron noise produced by the oscillation of one fuel assembly. Time-domain and frequency-domain approaches to the phenomena are compared. Numerical results show two different effects in the neutron noise. First, the neutron flux globally and slowly varies. Second, the neutron flux oscillates in-phase with the assembly vibration. Abstract: The mechanical vibrations of fuel assemblies have been shown to give rise to high levels of neutron noise, triggering in some circumstances the necessity to operate nuclear reactors at a reduced power level. This work analyses the effect in the neutron field of the oscillation of one single fuel assembly. Results show two different effects in the neutron field caused by the fuel assembly vibration. First, a global slow variation of the total reactor power due to a change in the criticality of the system. Second, an oscillation in the neutron flux in-phase with the assembly vibration. This second effect has a strong spatial dependence that can be used to localize the oscillating assembly. This paper shows a comparison between a time-domain and a frequency-domain analysis of the phenomena to calculate the spatial response of the neutron noise. Numerical results show a really close agreement between these two approaches.